EFEKTIVITAS PEMBELAJARAN MATEMATIKA MENGGUNAKAN METODE TPS (THINK-PAIR-SHARE) BERBASIS OPEN-ENDED-PROBLEM TERHADAP KREATIVITAS BELAJAR SISWA - Sri Hudia Rohmatin; Shahibul Ahyan (Universitas Sriwijaya, 2015)
This study was aimed at finding out whether or not Open-Ended-Problem Based TPS Method was effective on student’s mathematics learning creativity. The type of this research was quasi-eksperimental with one-group pretet posttest desaign. The sample of this research was 33 students. Instrument in form of 4 essay that was valid and reliable. Normality testing with Chi-kuadrat and homogeneity testing with Barlett-test while hypotesis testing with paramteric statistical analysis t-test. Based on the data analysis average pre test was 44 and post test was 64. The results of the normality testing pre-test group obtained x2count < x2tabel or 4.452 < 11.070 and post test group obtained x2count < x2tabel or 5,946 < 11.070. Data homogeneity testing results obtained x2count < x2tabel 2,484 < 3,841. The results of hypothesis testing data was obtained tcount > ttabel or 12,317 > 2,001. Based on the test results concluded that the hypothesis Ho was rejected and Ha accepted. To sum up, Open-Ended-Problem-Based TPS was significantly effective on student’s mathematics learning creativity. Key words: effectiveness, TPS method, open-ended-problem, students creativity DOI: http://dx.doi.org/10.22342/jpm.9.2.2085.178 - 187